2022
DOI: 10.1002/jia2.25932
|View full text |Cite
|
Sign up to set email alerts
|

A pretest‐posttest design to assess the effectiveness of an intervention to reduce HIV‐related stigma and discrimination in healthcare settings in Vietnam

Abstract: Introduction Stigma and discrimination are important barriers to HIV epidemic control. We implemented a multi‐pronged facility‐level intervention to reduce stigma and discrimination at health facilities across three high‐burden provinces. Key components of the intervention included measurement of stigma, data review and use, participatory training of healthcare workers (HCWs), and engagement of people living with HIV and key populations in all stigma reduction activities. Methods From July 2018 to July 2019, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…A study by Pollack et al . [51 ▪▪ ] evaluated a multipronged facility-level intervention in Vietnam that trained healthcare workers and used participatory approaches was able to decrease healthcare-associated HIV stigma (including discrimination and self-stigma). A pilot pragmatic trial targeting intersectional stigma among pregnant women living with HIV in Botswana found that the intervention led to a reduction in HIV-related stigma among participants, highlighting the importance of interventions that address structural issues that shape the experiences of individuals with multiple marginalized identities [52].…”
Section: Mitigating Stigma To Improve Uptake Of Hiv Servicesmentioning
confidence: 99%
“…A study by Pollack et al . [51 ▪▪ ] evaluated a multipronged facility-level intervention in Vietnam that trained healthcare workers and used participatory approaches was able to decrease healthcare-associated HIV stigma (including discrimination and self-stigma). A pilot pragmatic trial targeting intersectional stigma among pregnant women living with HIV in Botswana found that the intervention led to a reduction in HIV-related stigma among participants, highlighting the importance of interventions that address structural issues that shape the experiences of individuals with multiple marginalized identities [52].…”
Section: Mitigating Stigma To Improve Uptake Of Hiv Servicesmentioning
confidence: 99%
“…Without providing adequate privacy for HTS and PrEP delivery, it will be challenging to scale-up integration of PrEP in MCH in order to reach women with greatest need ( 46 , 47 ). In the literature, the majority of stigma-reduction interventions focus on reducing stigma among HCWs or reducing internalized stigma among people living with HIV; these methods include trainings for HCWs and popular opinion leaders, group education and trainings including people living with HIV, restructuring facility anti-discrimination policies, and rarely, social media campaigns ( 48 51 ). There is a need for stigma-reduction interventions that target people not living with HIV that will enable them to take full advantage of HIV prevention services.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals drew attention to the interconnected nature of public stigma, self-stigma, and a wide range of other challenges faced by PLWH that hinder access to healthcare services [32]. Pollack et al reported in their work that women living with HIV were more likely to report self-stigma (OR=1.85, 95% CI: 1.33-2.58) and to have experienced the disclosure of their serostatus by a healthcare professional without their consent (OR=1.60, 95% CI: 1.10-2.31) [40].…”
Section: Self-stigmamentioning
confidence: 99%